2018
DOI: 10.1177/0739986317751899
|View full text |Cite
|
Sign up to set email alerts
|

Latino Immigrant Home-Country Media Use and Participation in U.S. Politics

Abstract: This article examines the ways in which Latino immigrants' use of news media from their home countries influences their likelihood of participating in politics in the United States. Using data from the 2015 Latino National Health and Immigration Survey of 1,005 Latino adults in the United States, I run a set of multivariate analyses to determine whether home-country media use affects the likelihood that Latino immigrants, 52% of whom use home-country media at least a few times per week, will vote, participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Media and social media use were measured with three questions. Questions 1 and 3 measure what has been termed "home country media use" (Vidal, 2018;Yin, 2013). Question 2 measures "ethnic media use" (Yin, 2013), meaning migrants' connections to other migrants from their place of origin residing in the same country.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Media and social media use were measured with three questions. Questions 1 and 3 measure what has been termed "home country media use" (Vidal, 2018;Yin, 2013). Question 2 measures "ethnic media use" (Yin, 2013), meaning migrants' connections to other migrants from their place of origin residing in the same country.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, connected migrants are characterised by belonging to multiple networks, holding allegiances to several locations and cultures, and having hypermobility and flexibility on the labour market (Diminescu, 2008). Social media (Hofhuis et al, 2019;Yin, 2013) and news and current affairs programmes (Alencar & Deuze, 2017;Vidal, 2018) are often discussed in the literature in this context of changing migration networks through increased digital connectivity. Home country media and "ethnic" media that specifically targets migrants and provides them with information and news from their host country can strengthen migrants' connections to their place of origin and facilitate the development of new hybrid migrant identities (Yin, 2013).…”
Section: Connected Migrantsmentioning
confidence: 99%
“…While past research has chronicled various aspects of migrant life such as voting, workplace experiences, and remittance behavior (Duquette-Rury 2019; Gleeson 2012Gleeson , 2016Leal, Lee, and McCann 2012;Medina Vidal 2018;Apostolidis 2010), this focus tends to obscure the important role that civil society and other meso-level institutions play in helping migrants access rights and resources in their local communities. Supranational governing bodies have called on origin and sending states to ensure that migrant workers can access basic social security and services, though national enforcement instruments lack the ability to actually implement the rights encoded within the domestic laws of the receiving state.…”
Section: Constructing Portable Rights For Migrant Workersmentioning
confidence: 99%
“…Political engagement is another perspective that can be measured within the generational status. For instance, Latinx immigrants who reported watching news media from their country of origin, which usually focused on immigration and politics, endorsed a higher likeliness to participate in U.S. political practices (Vidal, 2018). Santoro and Segura (2011) found that younger generations of Latinx participants in their study maintained a lack of political interaction overall.…”
Section: Generational Differencesmentioning
confidence: 98%